THE ILLOCUTIONARY ACTS IN THE MOVIE THE DEATH CURE: PRAGMATICS STUDY - Eka x Eka Nur Ariesta; Ervina Simatupang (Lembaga Penelitian Universitas Pasundan, 2019)
Illocutionary act is part of speech acts which are something in order to do something as what the speaker intents. Based on Yule (1996: 48) stated that illusionary act is performed via the communicative force of utterance. Illocutionary act is a performance of act in saying something .Next, based on Vanderveken, Daniel (2009: 97) mentioned illocutionary acts of the meanings in the use and comprehension of language. The finding shows that the dialogue in the Death Cure movie contains each of illocutionary acts. They are representative illocutions, directives, illocutions, committees, expressives, and declarations. 2 types of strategies namely direct strategy, which has a literal meaning in the context and indirect strategy which has implicates in the context of speech, are used by speakers in uttering their speech. The data is taken from The Death Cure Movie. The method used in this thesis is the analytical descriptive- comparative method. It is used to get a clear and objective description of the Illocutionary in the movie.